Application of Mediterranean diet in cardiovascular diseases and Type 2 diabetes mellitus: motivations and challenges - Salim AlAufi, Najwa; Yoke, Mun Chan; Waly, Mostafa I.; Yit, Siew Chin; Barakatun-Nisak, Mohd Yusof; Ahmad, Norliza (MDPI, 2022)
Objective: Cardiovascular disease (CVD) is the leading cause of disability and death in many countries. Together with CVD, Type 2 diabetes mellitus (T2DM) accounts for more than 80% of all premature non-communicable disease deaths. The protective effect of the Mediterranean diet (MedDiet) on CVD and its risk factors, including T2DM, has been a constant topic of interest. Notwithstanding, despite the large body of evidence, scientists are concerned about the challenges and difficulties of the application of MedDiet. This review aims to explore the motivations and challenges for using MedDiet in patients with CVD and T2DM. Design: An electronic search was conducted for articles about MedDiet published in PubMed, ScienceDirect, Scopus, and Web of Science up to December 2021, particularly on CVD and T2DM patients. From a total of 1536 studies, the final eligible set of 108 studies was selected. Study selection involved three iterations of filtering. Results: Motivation to apply MedDiet was driven by the importance of studying the entire food pattern rather than just one nutrient, the health benefits, and the distinct characteristics of MedDiet. Challenges of the application of MedDiet include lacking universal definition and scoring of MedDiet. Influences of nutritional transition that promote shifting of traditional diets to Westernized diets further complicate the adherence of MedDiet. The challenges also cover the research aspects, including ambiguous and inconsistent findings, the inexistence of positive results, limited evidence, and generalization in previous studies. The review revealed that most of the studies recommended that future studies are needed in terms of health benefits, describing the potential benefits of MedDiet, identifying the barriers, and mainly discussing the effect of MedDiet in different populations. Conclusions: In general, there is consistent and strong evidence that MedDiet is associated inversely with CVD risk factors and directly with glycemic control. MedDiet is the subject of active and diverse research despite the existing challenges. This review informs the health benefits conferred by this centuries-old dietary pattern and highlights MedDiet could possibly be revolutionary, practical, and non-invasive approach for the prevention and treatment CVD and T2DM.